Improvement of Self-Esteem in Children with Specific Learning Disorders after Donkey-Assisted Therapy - Francesco Corallo; Lilla Bonanno; Davide Cardile; Francesca Luvarà; Silvia Giliberto; Marcella Di Cara; Simona Leonardi; Angelo Quartarone; Giuseppe Rao; Alessandra Pidalà (Children, 2023)
Dyslexia is a learning disorder related to receptive language characterized by difficulties with decoding, fluent word recognition, automatic naming skills and/or reading comprehension skills. It usually leads to severe functional impairment and the permanent need for support and interventions. Since animal-assisted interventions (AAIs) have been found to improve physical, emotional, cognitive and/or social functioning in humans, the aim of this study is to demonstrate the effectiveness of onotherapy on children with SLD by improving self-esteem and school performance. Sixteen patients with a diagnosis of dyslexia were randomly assigned to two treatment groups: the first was a conventional neuropsychological group therapy without onotherapy, and the second was a neuropsychological group therapy incorporating AAIs with therapy donkeys. The neuropsychological assessment included the WISC-IV, DDE and the TMA test, which were administered before and after the treatment in both groups. The results of the experimental group show significant improvement in word reading test correctness (p = 0.03) and speed (p = 0.03), non-word reading test speed (p = 0.01), reading text test correctness (p = 0.05) and speed (p = 0.03), word writing test correctness (p = 0.01), non-word writing test correctness (p = 0.02), writing sentences with homophonic words correctness (p = 0.01), interpersonal TMA (p = 0.04) and the total TMA (p = 0.04), which were significative. On the other hand, in the control group, significant differences were found in word reading test speed (p = 0.01), non-word reading test speed (p = 0.04), reading text test speed (p = 0.02), writing word test correctness (p = 0.01), writing non-word test correctness (p = 0.01) and writing sentences with homophonic words (p = 0.01). However, in this group, we observed no significant difference in the esteem of children. Training associated with the donkeys determined improved scholastic performances as far as reading is concerned and a change in self-esteem. Therefore, we can state that AAIs for dyslexia could be a viable and effective option to enhance the rehabilitation process, increase self-esteem and improve cognitive functions and language skills recovery.